Factors influencing uptake of schistosomiasis research findings in ingwavuma area, uMkhanyakude District, Kwazulu-Natal, South Africa - Tafadzwa Mindu; Moses J. Chimbari (AOSIS, 2021)
Background: Research uptake is concerned with spreading ideas across multiple levels of the community. Barriers such as poverty, lack of infrastructure, illiteracy and culture prevent information sharing in arid rural areas of sub-Saharan Africa. Objective: This study explores the factors influencing schistosomiasis research uptake and the available channels for the uptake of research findings from a transdisciplinary and eco-health research project on schistosomiasis in Ingwavuma area, uMkhanyakude district, KwaZulu-Natal province in South Africa. Methods: This case study conducted in 2017 involved 78 primary school children and 73 heads of household recruited through convenience and purposive sampling. Data were collected through focus group discussions, then transcribed and analysed by the researcher using thematic analysis. Results: Factors such as poor knowledge, water and sanitation problems, and lack of sufficient health workers hindered the uptake of schistosomiasis research findings. Participants recommended several platforms to share schistosomiasis research findings with the community, including: door to door visits; social gatherings such as sports events, talent shows, and religious gatherings; mass media platforms such as radio and television; social media platforms such as WhatsApp, Facebook and Twitter; and printed media such as posters, booklets and pamphlets. Conclusions: There is a need to train health workers and peer educators in this area of South Africa to educate people about schistosomiasis infection, screening and treatment through home visits or social events. Schistosomiasis research findings must be synthesised and packaged in different forms for dissemination via multimedia media-based communication channels.